Assessment of coping with illness among patients with hepatitis C - on example of research in Poland - Walery Zukow (Kazimierz Wielki University, 2023)
Introduction: In Poland approximately 2% of the population are infected with HCV. The majority (70-80%) of persons infected with HCV develop chronic hepatitis C which, when untreated, may lead to cirrhosis and/or hepatocellular carcinoma. The skills of coping with stress and acceptance of chronic illness may motivate patients for participation in treatment and leading a health-promoting life style. Objective: The aim of the study was assessment of coping with illness in patients with chronic hepatitis C. Materials and Method: The study included 220 adults with chronic hepatitis C, and was conducted by the method of a diagnostic survey using the Polish questionnaire: Brief Method of Assessment of Coping with Illness (Krótka Metoda Oceny Radzenia Sobie z Chorobą - KMORSZCH), the Acceptance of Illness Scale (AIS), and an author-constructed questionnaire. Results:  The examined group of patients with hepatitis C most strongly presented style oriented on emotions and passivity (mean score 1.20), and style focused on problem solving (mean score 1.05), followed by respondents who presented avoidance-oriented style (mean score 0.98), whereas the style focused on seeking the best solution to the problem was most rarely chosen (mean score 0.77). It was found that the more frequently the respondents presented style oriented on experiencing emotions and passivity, to the significantly lower degree they accepted their illness. Patients with higher education significantly more often presented style focused on seeking the best solution to the problem (p<0.045),while those with the lowest level of education significantly more frequently were oriented on experiencing emotions and passivity (p<0.001). Rural inhabitants significantly more often presented style oriented on experiencing emotions and passivity (p<0.002). The remaining independent variables: gender, age, marital status, number of years of illness, and occupational activity had an insignificant effect on the selection of the style of coping with hepatitis C.   Conclusions: The results of the study confirm the need for psychotherapeutic actions with respect to patients with hepatitis C in order to help them cope with the chronic disease, because they most often chose style oriented on emotions and passivity. Psychological assistance should be provided especially for the group of patients who have difficulty with acceptance of the illness.